2008
DOI: 10.1210/jc.2007-2636
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin-1α by Human Endometrial Stromal Cells Is Triggered during Menses and Dysfunctional Bleeding and Is Induced in Culture by Epithelial Interleukin-1α Released upon Ovarian Steroids Withdrawal

Abstract: Our experiments in cultured endometrium suggest that IL-1alpha released by epithelial cells triggers the production of IL-1alpha by stromal cells in a paracrine amplification loop to induce MMP-1 expression during menstruation and dysfunctional bleeding. All three steps of this amplification cascade are repressed by EP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…However, menstruation starts in response to a drop in P concentration whereas proliferative explants barely contain P before culture. Tissue sampling for culture likely induces signaling cascades and/or allows the release of intracellular stocks of cytokines, such as IL-1␣, which is present in epithelial cells throughout the menstrual cycle and is able to stimulate MMP expression by stromal cells (6).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, menstruation starts in response to a drop in P concentration whereas proliferative explants barely contain P before culture. Tissue sampling for culture likely induces signaling cascades and/or allows the release of intracellular stocks of cytokines, such as IL-1␣, which is present in epithelial cells throughout the menstrual cycle and is able to stimulate MMP expression by stromal cells (6).…”
Section: Figmentioning
confidence: 99%
“…To further characterize the mechanisms controlling the local extent of endometrium remodeling during menstruation, we recently compared transcriptomes between degraded and preserved areas (4). This study highlighted major differences in gene expression profiles between stroma and glands, which could reflect or result from paracrine interactions between the two tissue compartments, as exemplified by the focal expression of stromal MMP-1 in response to epithelial IL-1␣ released at the onset of menstruation (3,5,6).…”
mentioning
confidence: 99%
“…First, the expression of several MMPs is controlled by EP (3) and by soluble local regulators such as IL-1␣ (4,5), LEFTY-A (6), and TGF-␤ (7). Second, being synthesized as inactive zymogens, MMPs must be activated by proteolytic propeptide removal (8).…”
mentioning
confidence: 99%
“…It has been demonstrated that secretion of MMP-1, MMP-3 and MMP-9 is stimulated by TNF-β and interleukin-1. In contrast, MMP-2 is independent of such cytokines [6,7].…”
Section: The Structure and Function Of Matrix Metalloproteinases And mentioning
confidence: 96%